Phenotypic characterization of papaya genotypes to determine powdery mildew resistance - Vivas,Marcelo (2017)
Abstract In support of breeding of papaya (Carica papaya), the disease incidence and severity of powdery mildew (Ovulariopsis caricicola) were evaluated in papaya genotypes. Two experiments in complete randomized blocks were carried out, one in the field and the other in a greenhouse. In field experiments, the lowest mean disease incidence was observed on the genotypes ‘Costa Rica’ and ‘Baixinho Super’, and the lowest mean disease severity on ‘Caliman M5’, ‘GTF’, ‘SH 11-08’, and ‘JS 11’. In the greenhouse experiment, the genotypes ‘Caliman M5’, ‘Golden’, ‘Kapoho Solo’, ‘Waimanalo’, ‘Mamão Bené’, ‘SH 12-07’, ‘JS 12’, and ‘GTF’ had the lowest mean incidence in at least one evaluation. On the other hand, for severity, the genotypes ‘Diva’, ‘Sunrise Solo 72/12’, ‘Kapoho Solo PA’, ‘Waimanalo’, ‘Maradol’, ‘Maradol GL’, ‘SH 15-04’, ‘FMV, ‘JS 12-4’, ‘SH 12-07’ and ‘Sekati FLM’ had the lowest means. These results indicate these genotypes for a possible use in breeding for reduction of powdery mildew intensity.